A Polyphenol-Rich Extract of Olive Mill Wastewater Enhances Cancer Chemotherapy Effects, While Mitigating Cardiac Toxicity - Albini, Adriana; Festa, Marco M. G.; Ring, Nadja; Baci, Denisa; Rehman, Michael; Finzi, Giovanna; Sessa, Fausto; Zacchigna, Serena; Bruno, Antonino; Noonan, Douglas M. (Frontiers in Pharmacology, 2021)
Cardiovascular toxicity remains one of the most adverse side effects in cancer patients receiving chemotherapy. Extra-virgin olive oil (EVOO) is rich in cancer preventive polyphenols endowed with anti-inflammatory, anti-oxidant activities which could exert protective effects on heart cells. One very interesting derivative of EVOO preparation is represented by purified extracts from olive mill waste waters (OMWW) rich in polyphenols. Here, we have investigated the anti-cancer activity of a OMWW preparation, named A009, when combined with chemotherapeutics, as well as its potential cardioprotective activities. Mice bearing prostate cancer (PCa) xenografts were treated with cisplatin, alone or in combination with A009. In an in vivo model, we found synergisms of A009 and cisplatin in reduction of prostate cancer tumor weight. Hearts of mice were analyzed, and the mitochondria were studied by transmission electron microscopy. The hearts of mice co-treated with A009 extracts along with cisplatin had reduced mitochondria damage compared to the those treated with chemotherapy alone, indicating a cardioprotective role. To confirm the in vivo results, tumor cell lines and rat cardiomyocytes were treated with cisplatin in vitro, with and without A009. Another frequently used chemotherapeutic agent 5-fluorouracil (5-FU), was also tested in this assay, observing a similar effect. In vitro, the combination of A009 with cisplatin or 5-FU was effective in decreasing prostate and colon cancer cell growth, while it did not further reduce growth of rat cardiomyocytes also treated with cisplatin or 5-FU. A009 cardioprotective effects towards side effects caused by 5-FU chemotherapy were further investigated, using cardiomyocytes freshly isolated from mice pups. A009 mitigated toxicity of 5-FU on primary cultures of mouse cardiomyocytes. Our study demonstrates that the polyphenol rich purified A009 extracts enhance the effect of chemotherapy in vitro and in vivo, but mitigates chemotherpy adverse effects on heart and on isolated cardiomyocytes. Olive mill waste water extracts could therefore represent a potential candidate for cardiovascular prevention in patients undergoing cancer chemotherapy.